Comerciantes españoles en los albores del Perú republicano. Entre la persecución y la supervivencia, 1824-1828 - Ruiz de Gordejuela Urquijo, Jesús (2015)
This article discusses how Cadiz merchants conducted their trade with Peru during the transit from colonial to republican times. The basis for describing this brief but intense period is the unpublished correspondence of Francisco de Carranza, a direct witness of the events of that time. As a result of the difficulties that marked those years, merchants increasingly resorted to fraudulent practices like forging invoices or using fake certificates to introduce Spanish goods in Peru.